Acute supraglottitis in adults. Issue 6 (June 2018) - Whittaker, Joshua D; Jolly, Karan
Supraglottitis is a rare life-threatening paediatric disease whose occurrence has declined with the rise of immunization; however, it remains an important clinical diagnosis in the adult population. It is vital to consider in patients presenting with an acute sore throat. Misdiagnosis can lead to serious morbidity. This article will review the pathophysiology of supraglottitis, explain the changing demographics of the disease, important clinical features and management particularly where relevant to presentation in general practice.